Iran’s First Pivot to ASEAN, 1997–2005: Corridor Diplomacy and a Deferred Partnership - Danial Khataei (International Journal of Asia Pacific Studies, 2026)
Over the past three decades, the Association of Southeast Asian Nations (ASEAN) has occupied a recurrent yet understudied place in the foreign policy of the Islamic Republic of Iran. While Iranian leaders have consistently signalled interest in developing relations with Southeast Asia, existing scholarship on Iran’s Asia-Pacific policy has largely prioritised Tehran’s relations with China or individual ASEAN member states. There is a pressing need for a deeper analysis of the roots of Iran’s political and economic interest in ASEAN, the history of Iran-ASEAN relations and the evolution of Iran’s overall policy towards Southeast Asia. This article examines Iran’s first pivot towards ASEAN during the presidency of Mohammad Khatami (1997–2005). It argues that during this period, Iran made its first concerted effort to improve relations with ASEAN states and to leverage the ensuing momentum to secure Sectoral Dialogue Partner status with ASEAN. Iran launched numerous energy, transport, and logistics projects in Southeast Asia, and ASEAN states likewise initiated projects in Iran’s energy and logistics sectors. Iran’s bilateral deals with ASEAN states should be viewed as part of a coordinated corridor strategy rather than a set of isolated deals. The findings indicate that Iran sought to present itself to ASEAN leaders as a reliable energy partner and the optimal gateway to Central Asia, while addressing older security concerns about Iranian involvement with militant groupings in Southeast Asia and the export of Shia ideology. Methodologically, this article employs a qualitative historical approach, combining multi-archival research with process tracing across Iranian and ASEAN sources.